The Effects Of Photoperiods And Light Emitting Diodes (Leds) On Cell Suspension And Hairy Root Cultures Of Eurycoma Longifolia Jack - Sani, Sale (2024)
Eurycoma longifolia Jack, commonly known as Tongkat Ali, is a Southeast Asian multipurpose medicinal tree used for treating various ailments, including diarrhea, leukemia, and malaria, as well as chronic diseases like diabetes and cancer. Tongkat Ali is of high demand especially for its aphrodisiac properties, but production is limited by long gestation periods and dependence on wild populations. In vitro cultivation systems, such as cell suspension and hairy root cultures, provide promising alternatives for sustainable production. This study aims to enhance the growth and production of bioactive metabolites, including eurycomanone, 9-hydroxycanthin-6-one, and 9-methoxycanthin-6-one, in cell suspension and hairy root cultures of E. longifolia using photoperiods and light-emitting diodes (LEDs) treatments. Cell suspensions were derived from internodal explants, and hairy roots were obtained from the Forest Research Institute Malaysia (FRIM). The cell suspension cultures were subjected to 24-hour continuous light and a 16/8-hour light/dark cycle as a control. Similarly, the hairy root cultures were exposed to 24-hour light, 16/8-hour light/dark, and 24-hour darkness as a control. Both cultures were also treated with blue, red, and blue+ red LED lights, with white LED as control. Growth morphology, bioactive metabolite synthesis, total flavonoid content and antioxidant activity were assessed. The results have shown that cell suspension cultures under 24-hour light have significantly higher dry weight of 0.13 g/50 mL after 15 days and produced higher levels of eurycomanone (8.96 μg/g DW) and 9-hydroxycanthin-6-one (0.29 μg/g DW) after 18 days.